Mutation and updating of land records in Bangladesh: a study at Gazipur sadar upazila - Islam, Muhammad Ariful (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.